2000
DOI: 10.1111/j.1095-8649.2000.tb00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adjustments in the common carp during prolonged hypoxia

Abstract: Biochemical and respiratory changes in the common carp Cyprinus carpio were studied 6, 24, 96 and 168 h upon exposure to hypoxia (0·5 mgO 2 l 1 ). Modification of kinetic properties of phosphofructokinase (PFK-1), coupled with a decreased in PFK-1 activities, were evident in muscle. No changes in kinetics and activities could be observed in muscle pyruvate kinase (PK) and lactate dehydrogenase (LDH). A decrease in muscle citrate synthase (CS) and an increase in muscle cytochrome c oxidase (CCO) were found. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 32 publications
3
31
1
Order By: Relevance
“…Elevation of these ratios suggests that when snapper are chronically challenged by low P O2 (10.2-12.1kPa), anaerobic systems may compensate for constrained aerobic ATP synthesis. Similar increases in anaerobic potential have been observed in other species of fish exposed to periods of chronic hypoxia (Greaney et al, 1980;Johnston and Bernard, 1982;Ton et al, 2003;Yang et al, 1992;Zhou et al, 2000), but not in others (Driedzic et al, 1985;Martínez et al, 2006;Zhou et al, 2000). Whilst these adjustments in anaerobic enzyme activity were possibly important to snapper during moderate long-term hypoxia (10.2-12.1kPa), hypoxia-acclimated fish in the behavioural trials also showed signs of improved low-O 2 tolerance at sub-critical P O2 levels (<7kPa), where fish would likely struggle to meet basal…”
Section: Are Anaerobic Adjustments Responsible For Improved Hypoxia Tsupporting
confidence: 56%
“…Elevation of these ratios suggests that when snapper are chronically challenged by low P O2 (10.2-12.1kPa), anaerobic systems may compensate for constrained aerobic ATP synthesis. Similar increases in anaerobic potential have been observed in other species of fish exposed to periods of chronic hypoxia (Greaney et al, 1980;Johnston and Bernard, 1982;Ton et al, 2003;Yang et al, 1992;Zhou et al, 2000), but not in others (Driedzic et al, 1985;Martínez et al, 2006;Zhou et al, 2000). Whilst these adjustments in anaerobic enzyme activity were possibly important to snapper during moderate long-term hypoxia (10.2-12.1kPa), hypoxia-acclimated fish in the behavioural trials also showed signs of improved low-O 2 tolerance at sub-critical P O2 levels (<7kPa), where fish would likely struggle to meet basal…”
Section: Are Anaerobic Adjustments Responsible For Improved Hypoxia Tsupporting
confidence: 56%
“…The liver plays a key role in the hypoxia-adaptation of the common carp, primarily through the up-regulation of anaerobic metabolism (15,16). We now provide another potentially important hypoxia-adaptive response in this tissue, namely the substantial up-regulation of MYG-1 protein expression in liver and other nonmuscle tissues through a transcriptional mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…Higher values, however, such as those detected in ponds with tube well water, are able to affect fish metabolism [32], causing physiological changes and reduced growth [33], although increased mortality was not reported. Besides salinity, carp is also tolerant to low levels of DO and can survive for more than 7 days in the water with 0.5 mg/L of DO [34]. COD levels were high, as compared to natural freshwater, but these levels are tolerated in semi-intensive aquaculture and are related to the quantity of supplemented feed [27].…”
Section: Discussionmentioning
confidence: 99%